1985
DOI: 10.1007/bf02266952
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethylene on adventitious root formation in mung bean (Vigna radiata) cuttings

Abstract: Abstract.A promotive effect of ethylene on the formation of adventitious roots by mung bean cuttings was demonstrated using a recirculating solution culture system to apply dissolved ethylene. The number of roots increased in proportion to the length of exposure to the gas. Mean root numbers per cutting for a 4-day exposure to ethylene and an air control were 45 and 19, respectively. The tissue was most sensitive to a 24-h ethylene '~pulse" 2-3 days after taking cuttings. Rooting was maximal at a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…5) the number of roots which are formed, it does not appear that these phenomena are causally associated. As previously shown in mung bean (12), application of exogenous ethylene to chrysanthemum cuttings stimulated, rather than inhibited root growth. In aerobic media, ethylene also resulted in greater root initiation.…”
Section: Effect Of Ethylene and Oxygen Treatment On Rootingsupporting
confidence: 71%
See 1 more Smart Citation
“…5) the number of roots which are formed, it does not appear that these phenomena are causally associated. As previously shown in mung bean (12), application of exogenous ethylene to chrysanthemum cuttings stimulated, rather than inhibited root growth. In aerobic media, ethylene also resulted in greater root initiation.…”
Section: Effect Of Ethylene and Oxygen Treatment On Rootingsupporting
confidence: 71%
“…Movement of ACC to the aerial portions of the plant in the transpiration stream and its oxidation there to ethylene results in the epinastic symptoms commonly observed in waterlogged plants (2). Although ethylene has been reported to stimulate adventitious rooting in Mung bean cuttings (12), ' the growth of roots is very sensitive to ethylene (6), being first stimulated, and then inhibited, as the concentration of ethylene in the medium increases. It has recently been shown that high concentrations of ACC inhibit root production (8).…”
mentioning
confidence: 99%
“…These promoting effects of auxin and ethylene are commonly found with respect to adventitious root formation in soft-and hard-wooded cuttings (e.g. Gurumurti, Gupta and Kumar, 1985;Robbins et al, 1985;Bollmark and Eliasson, 1990;Nordstrom and Eliasson, 1991;Selby, Kennedy and Harvey, 1992).…”
Section: Resultsmentioning
confidence: 92%
“…These include control of stem growth inhibition during the quiescence response in submergence-resistant rice plants as well as rapid stem growth, which helps deepwater rice to escape flooding (Xu et al, 2006;Hattori et al, 2009). Furthermore, ethylene promotes growth of adventitious roots in rice (Lorbiecke and Sauter, 1999;Steffens et al, 2006), Rumex palustris (Peeters et al, 2002), Vigna radiata (Robbins et al, 1985), and tomato (Solanum lycopersicum) (Phatak et al, 1981). Ethylene insensitivity resulted in the formation of fewer adventitious roots in tobacco (Nicotiana tabacum) (McDonald and Visser, 2003) and in reduced growth of adventitious roots in petunia (Petunia 3 hybrida) (Clark et al, 1999).…”
Section: Introductionmentioning
confidence: 99%